Acyclic αγα-tripeptides with fluorinated- and nonfluorinated-furanoid sugar framework: importance of fluoro substituent in reverse-turn induced self-assembly and transmembrane ion-transport activity - Burade, S. S.; Shinde, S. V.; Bhuma, N.; Kumbhar, N.; Kotmale, A.; Rajamohanan, P. R.; Gonnade, R. G.; Talukdar, P.; Dhavale, D. D. (Journal Of Organic Chemistry, 2017)
Acyclic αγα-tripeptides derived from fluorinated-furanoid sugar amino acid frameworks act as reverse-turn inducers with a U-shaped conformation, whereas the corresponding nonfluorinated αγα-tripeptides show random peptide conformations. The NMR studies showed the presence of bifurcated weak intramolecular hydrogen bonding (F···HN) and N+···Fδ- charge-dipole attraction compel the amide carbonyl groups to orient antiperiplanar to the C-F bond, thus, demonstrating the role of the fluorine substituent in stabilizing the U-shaped conformation. The NOESY data indicate that the U-shaped tripeptides self-assembly formation is stabilized by the intermolecular hydrogen bonding between C=O···HN with antiparallel orientation. This fact is supported by ESI-MS data, which showed mass peaks up to the pentameric self-assembly, even in the gas phase. The morphological analysis by FE-SEM, on solid samples, showed arrangement of fibers into nanorods. The antiparallel self-assembled pore of the fluorinated tripeptides illustrates the selective ion-transport activity. The experimental findings were supported by DFT studies.